Pengembangan Media Pembelajaran Powerpoint Interaktif berbasis Inkuiri Terbimbing pada Materi Reaksi Redoks Kelas XII SMA/MA - Auza Fadila Mumri; Syamsi Aini (Universitas Negeri Padang, 2019)
The 2013 curriculum is implemented in senior high school, emphasizing the scientific approach. Learning model that is able to make students active and can develop science process skills is guided inquiry. Guided inquiry consists of several syntax that can guides students in learning process, consisting of orientation, exploration, concept formation, application, and closing. Students are guided by key questions related to redox reaction material of class XII SMA or MA which is applied in instructional media in the form of interactive powerpoints. The type of this research was reseach and development with 4-D models. Powerpoint interactive validity testing is carried out by 3 chemistry lecturers at FMIPA UNP and 2 chemistry teachers at SMAN 14 Padang, the powerpoint interactive have an average kappa moments 0.91 which is very high level of validity. While the module practicality test is by 3 chemistry teachers and 25 XII grade IPA at SMAN 14 Padang, the average kappa moment from the results of practicality test of the module by the teachers is 0.93 and by the student is 0.90 with very high category. From the research can be concluded that interactive powerpoint is valid and practical.